Authenticating Drivers Using Automotive Batteries - He, Liang; Shu, Yuanchao; Lee, Youngmoon; Chen, Dongyao; Shin, Kang G. (The Proceedings of the ACM on Interactive, Mobile, Wearable and Ubiquitous Technologies (UbiComp), 2021)
Automakers have been improving, or even trying to replace, key-based driver authentication solutions, owing to their vulnerability to cyber attacks and single-point-of-failures, as well as their inability of driver identification. In line with this effort, we design a novel driver authentication system using automotive batteries, called Batteries-as-Authenticators (BAuth), to mitigate the limitations of key-based solutions by providing a second-factor authentication. BAuth is an add-on module installed between vehicles and their batteries, which uses the batteries as sensors to validate drivers' identities and actuators to enable/disable the cranking of vehicle's engine. We have prototyped and evaluated BAuth on 6 regular/hybrid/electric vehicles. Our evaluation shows BAuth to authenticate the drivers with a 98.17 (2.84)% averaged true (false) positive rates and tolerate the dynamics caused by the aging/temperature/state-of-charge of batteries. Our user study corroborates BAuth's attractiveness to car owners.